2008
DOI: 10.1038/ki.2008.230
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia due to follow-on epoetin

Abstract: A 57-year-old man with end-stage renal disease secondary to chronic interstitial nephritis was initiated on hemodialysis in February 2006 for uremic symptoms. In April 2006, his hemoglobin (Hgb) was 10.7 g/dl and transferrin saturation was 12.7%. He was started on subcutaneous follow-on epoetin-alfa, Wepox (Wockhardt Limited India, Mumbai, India) and 10 weekly doses of 100 mg each of iron sucrose administered intravenously. His Hgb increased to 12.3 g/dl within 2 months after the initiation of epoetin. He then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Reports of safety issues with some of these products, such as recombinant erythropoietins, have raised concerns about the quality of these biologics. [45][46][47][48] For example, increased rates of pure red-cell aplasia were observed in patients with chronic kidney disease who received subcutaneous administration of recombinant human erythropoietin compared with the reference product. Such adverse reaction appeared associated with an increased immunogenicity of the biologic product, with induction of anti-erythropoietin antibodies and pure red-cell aplasia in treated patients.…”
Section: International Nonproprietary Names and Naming Of Biosimilarsmentioning
confidence: 99%
“…Reports of safety issues with some of these products, such as recombinant erythropoietins, have raised concerns about the quality of these biologics. [45][46][47][48] For example, increased rates of pure red-cell aplasia were observed in patients with chronic kidney disease who received subcutaneous administration of recombinant human erythropoietin compared with the reference product. Such adverse reaction appeared associated with an increased immunogenicity of the biologic product, with induction of anti-erythropoietin antibodies and pure red-cell aplasia in treated patients.…”
Section: International Nonproprietary Names and Naming Of Biosimilarsmentioning
confidence: 99%
“…It has been shown that the quality of different non-innovator/copy products can vary signifi cantly and even different batches of what appears to be the same product can differ, with implications for both effi cacy and safety [10,18,19,20]. It is therefore imperative that clear terminology is used to accurately describe the nature and particularly the regulatory procedure used for particular biologicals.…”
Section: Generics and Biosimilars Initiative Journalmentioning
confidence: 99%
“…A case of pure red cell aplasia (PRCA) in an end-stage renal disease patient associated with induction of antibodies to administered erythropoietin (EPO) was described in India [10]. The patient had received the EPO product Wepox (Wockhardt Limited, India) which is referred to as a 'follow-on' product.…”
mentioning
confidence: 99%
“…However, the EU leaves a broad margin of discretion to each member state concerning substitution. The introduction of biosimilars into clinical practice may affect patient safety, as can be seen from the fact that a small change in the manufacture of epoetin alfa in the late 1990s led to an upsurge in the number of cases of pure red cell aplasia (PRCA) [12], and other cases have also been described in patients receiving s.c. copies of epoetin alfa manufactured outside the EU [13,14]. Given these concerns, the EMA requires registration studies of s.c. biosimilars before approving this route of administration; however, one such study of HX575 was halted for safety reasons following one case of PRCA and one case of anti-rHuEPO antibody positivity [15].…”
Section: Short-acting Epoetinsmentioning
confidence: 99%